Effectiveness of Showdown Strategy Games to Improve Students’ Reading Comprehension at Junior High School - Santika, Ira Ari; Hawa , Faiza; Yulianti, Fitri (Perkumpulan Alumni dan Santri Mahyajatul Qurro’, 2022)
This research is pre-experimental research that aims to determine the extent of students' reading comprehension skills before and after being taught using showdown strategy games. The research methodology is a quantitative method approach. The sample of this study was 34 students of class VIII A SMP N 1 Banjarharjo. The research instrument was in the form of tests, namely pre-test and post-test. In this study, the researcher used in Indonesian KKM (kriteria ketuntasan minimal) at SMPN 1 Banjarharjo with the criteria for the KKM score of 75. Based on the pre-test reading comprehension of students before being taught using the Showdown strategy, 8.82% met the KKM criteria, and the results of the pre-test reading comprehension of students after being taught using the Showdown strategy were 76,47% fulfilling the KKM criteria. Furthermore, the researchers also used the N-Gain formula to determine the effectiveness of the showdown strategy implementation. The results of the N-Gain calculation obtained a mean value of 68.3333. It can be concluded that there is a significant difference between students' reading abilities before and after being taught using showdown strategy games.